The Development of Herbicide Resistance Crop Plants Using CRISPR/Cas9-Mediated Gene Editing - Dong, Huirong (Genes (Basel), 2021)
The rapid increase in herbicide-resistant weeds creates a huge challenge to global food security because it can reduce crop production, causing considerable losses. Combined with a lack of novel herbicides, cultivating herbicide-resistant crops becomes an effective strategy to control weeds because of reduced crop phytotoxicity, and it expands the herbicidal spectrum. Recently developed clustered regularly interspaced short palindromic repeat/CRISPR-associated protein (CRISPR/Cas)-mediated genome editing techniques enable efficiently targeted modification and hold great potential in creating desired plants with herbicide resistance. In the present review, we briefly summarize the mechanism responsible for herbicide resistance in plants and then discuss the applications of traditional mutagenesis and transgenic breeding in cultivating herbicide-resistant crops. We mainly emphasize the development and use of CRISPR/Cas technology in herbicide-resistant crop improvement. Finally, we discuss the future applications of the CRISPR/Cas system for developing herbicide-resistant crops.